2018
DOI: 10.4314/jfas.v9i5s.73
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors contributing to musculoskeletal disorder among garage worker in Malaysia

Abstract: Maintenance involves task that is performed occasionally with exceptional conditions. This Shoulder, neck, wrist/hand, feet, low back and waist were among the body parts that recorded high percentage of developing bellow, pain and discomfort. Data gaps include lack of information regarding the prevalence of MSDs in garage worker

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 1 publication
2
10
2
4
Order By: Relevance
“…Not having professional training, moving loads of greater than 20 kg, repetitive tasks, force exertion, and job stress were significantly associated with the prevalence of WMSDs. e 47.7% annual prevalence of WMSDs obtained in this study was lower than the annual prevalence of WMSD reported in studies conducted in Malaysia (87.4%), India (58%), and Bangladesh (77%) [13,15,16]. A comparison of this finding with the findings of other surveys in musculoskeletal epidemiology should take into account the differences in epidemiologic case definitions that may exist among the different studies.…”
Section: Prevalence Of Work-related Musculoskeletal Disorderscontrasting
confidence: 63%
See 4 more Smart Citations
“…Not having professional training, moving loads of greater than 20 kg, repetitive tasks, force exertion, and job stress were significantly associated with the prevalence of WMSDs. e 47.7% annual prevalence of WMSDs obtained in this study was lower than the annual prevalence of WMSD reported in studies conducted in Malaysia (87.4%), India (58%), and Bangladesh (77%) [13,15,16]. A comparison of this finding with the findings of other surveys in musculoskeletal epidemiology should take into account the differences in epidemiologic case definitions that may exist among the different studies.…”
Section: Prevalence Of Work-related Musculoskeletal Disorderscontrasting
confidence: 63%
“…e final sample size for objective one was 188 vehicle repair workers. Considering a 10% nonresponse rate, the final sample size was 207. e sample size for the second objective was obtained by using a double population formula using factors that had strong associations with the outcome of interest in other literatures [15]. Finally, the largest sample size obtained was the one calculated for the second objective (n � 306) and thus used as a final sample size of the study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations